Enhancement of Biogas Production Through Solid-State Anaerobic Co-Digestion of Food Waste and Corn Cobs - Shitophyta, Lukhi Mulia; Salsabila, Anisa; Putri, Firanita Angraini; Jamilatun, Siti (UI Scholars Hub, 2022)
Although biogas has been primarily produced through liquid anaerobic digestion, this method leads to the floating and stratification of fibers and non-homogeneous mixing, which can reduce the biogas yield. Alternatively, biogas can be produced by the solid-state anaerobic digestion (SS-AD) of organic material with a high solid content, such as corn cobs. We investigated the co-digestion of food waste and corn cobs as a biomass feedstock for SS-AD in biogas production. We measured the effects of the total solid (TS) content, percentage of food waste, and reduction in volatile solids (VS), from which we determined its appropriate kinetic model. We found that the SS-AD of food waste with corn cobs produced a high biogas yield of 543 mL/g VS at a TS content of 22% and a food waste content of 20%. The first-order kinetics model for biogas production during SS-AD of the tested corn cob and food waste yielded an R2 value in the range of 0.91–0.94. The main contributor to the biogas production during the SS-AD of the corn cobs and food waste was the reduction in VS. A positive linear relationship was observed between the biogas yield and the reduction of VS.